Análisis jurídico del derecho de repetición en la legislación ecuatoriana. - Mera Álvarez, José Luis (2013)
This work of graduation was developed in a text that allows to interpret the reality of the problem on the Right of Repetition, in the Ecuadoran Legislation. The investigation has research analyze how agility the procedures that can be made through a good operation that offers a vision of Ecuadorian group, by the scene designed by the conflicting that give as in the legal aspect, economic and very little social in the social one. This shall be understood as a process that is through study in the Ecuadorian legislation, inside this work a descriptive research was conducted using a methodology of scientific questions, methods, such as the inductive, deductive, analytical and synthetic applied in the texture of this thesis.